Confidence and College Applications: Evidence from a Randomized Intervention - Rustamdjan Hakimov; Renke Schmacker; Camille Terrier (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
This paper investigates the role self-confidence plays in college applications. Using incentivized experiments, we measure the self-confidence of more than 2,000 students applying to colleges in France. This data reveals that the best female and low-SES students significantly underestimate their rank in the grade distribution compared to male and high-SES students. By matching our survey data with administrative data on real college applications and admissions, we show that miscalibrated confidence affects college choice on top of grades. We then estimate the impact of a randomized intervention that corrects students' under- and overconfidence by informing them of their real rank in the grade distribution. The treatment reduces the impact of under- and overconfidence for college applications, to the point where only grades but not miscalibrated confidence predict the application behavior of treated students. Providing feedback also makes the best students, who were initially underconfident, apply to more ambitious programs with stronger effects for female and low-SES students.
Keywords: I24; J24; D91; C90; 330; matching mechanism; confidence; information treatment; survey experiment